CHILDREN LANGUAGE ACQUISITION PROCESS - Loli Safitri (English Department of Faculty of Tarbiyah and Teacher Training, 2020)
This research discusses a case study of children in acquiring their first language at age 18 months old in Bukittinggi. The process deals with some stages namely cooing, babbling, holophrastic, the two-word stage, telegraphic stage, and multiword stage. The purpose of this study is focused on how the children learn the language in the real life. To find out the answer of the problem in this research, the researcher uses the related theories, they are Lyons (1981), Varshney (2003), Chomsky (2009), Bolinger (2002), Gleason (1998), Steinberg (2003), Fromkin (1983), Bolinger (2002) and Steinberg (2003). This research is conducted with descriptive qualitative research where the subject and object is taken from the children at age 18 months old in Bukittinggi. The researcher takes the observed baby named Azka as the subject and gets the data by observation and video recording. After the data had been collected, the researcher finds out that Azka was 18 months old baby who was in holophrastic functions: the one-word utterances stage of language development. Finally, parents’ role is important to develop the children language. The parents should build interaction with their child to know their child’s language development. Besides that, the researcher suggests the parents to say the right pronunciation to the children.